THE EFFECT OF HIGH DOSE AND LOW DOSE PREGABALIN AS PREMEDICATION ON PREOPERATIVE ANXIETY AND SEDATION LEVELS - Zafar, Ayman; Farhat, Kulsoom; Saeed, Mobasher Ahmed; Khan, Waqar Aslam; Ali, Shabana; Ata, Nausheen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the role of pregabalin as premedication for preoperative sedation & anxiolysis with two different doses in laparoscopic cholecystectomy patients. Study Design: Prospective, randomized control study Place and Duration of Study: Department of Pharmacology and Therapeutics, Army Medical College, Rawalpindi in collaboration with Department of Anesthesiology, CMH, Rawalpindi from February 2019 to July 2019. Patients & Methods: 96 patients of either gender, aged between 18 to 60 years with ASA grade I-II, undergoing elective laparoscopic cholecystectomy were enrolled in this study. They were randomly divided into three groups having 32 patients each. Group 1 received oral placebo drug, Group 2 received oral pregabalin 150 mg, whereas Group 3 received oral pregabalin 300mg with sip of water 90 mins before the induction of general anesthesia. The effects of drugs on the patient’s level of sedation and anxiety were evaluated at baseline and before the induction of anesthesia using Ramsay Sedation Score and Beck Anxiety Inventory respectively. Results: Premedication with pregabalin 150mg and 300mg significantly produced sedation as compared to placebo. Though, pregabalin 300mg exhibited more sedation than pregabalin 150mg but the difference between them was statistically insignificant (p >0.05). Preoperative administration of pregabalin was related with anxiolysis, with the most prominent results shown by pregabalin 300mg (p <0.05) whereas pregabalin 150mg couldn’t alleviate anxiety and the results were statistically insignificant (p >0.05). Conclusions: Premedication with pregabalin 300mg, 90 mins before the induction of general anesthesia is an effective regimen to alleviate preoperative anxiety and sedation.